Effect of various culture media on mycelium growth andSporulation of dermatophytes isolated from the Patients of sms hospital,jaipur, rajasthan - SACHIN KUMAR; SEEMA BHADAURIA (International Journal of Pharma and Bio Sciences, 2017)
Earth has been documented as a natural area for fungi which found as individual kingdom through innovation. In their growth, different culture media significantly affected mycelium and sporulation. The present investigation was conducted to examine the effect of different broth media on the mycelial growth and fungal sporulation of Trichophyton rubrum and Microsporum gypseum. In the present study, Mannitol Salt Broth was found suitable for the growth of T. rubrum and M. gypseum followed by others broths for each one with a flotation towards the alkaline range.